Non-Economic Motivations behind International Student Mobility: An Interdisciplinary Perspective - Tokas, Shekhar; Sharma, Anand; Mishra, Ratnam; Yadav, Rohit (Journal of International Students, 2022)
International Student Mobility (ISM) has received a lot of attention in the literature on international migration. However, most of the studies assume that investment in skills and knowledge by international students is guided by economic motivations only. Importantly, with an increase in the proportion of international student mobility in total mobility, the students’ motivations have become more complex. Different theoretical approaches across disciplines have been logically extended to study the mobility motivations of international students. Most of the existing approaches do not emphasise the non-economic aspects of motivation and thus, do not provide a holistic understanding of ISM. This paper proposes an augmented human capital framework that incorporates the non-economic motivations of international students through the inclusion of psychic gains and the acquired stocks of personal and social capital.